2022
DOI: 10.1155/2022/2798217
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology and Molecular Docking Analysis to Explore the Mechanism of Huaiqihuang-Mediated Alleviation of Henoch–Schönlein Purpura Nephritis

Abstract: Objective. Henoch–Schönlein purpura nephritis (HSPN) is considered a major cause of chronic renal failure and is the most common secondary glomerular disease in children. Huaiqihuang (HQH), a traditional Chinese herbal formula, exhibits therapeutic effects against HSPN in clinical practice. However, the potential molecular targets and mechanisms underlying HSPN treatment remain unclear. Methods. By constructing a protein-protein interaction (PPI) network, core targets related to HQH and HSPN were identified. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…HQH can alleviate cyclophosphamide-induced nephrotoxicity by suppressing the MAPK/NF-κB pathway and NLRP3 inflammasome activation [31]. Liu's study showed AKT1, MMP9, and SERPINE1 may be vital in treating HSPN using Network Pharmacology and Molecular Docking Analysis [34]. HQH granules are mainly composed of Trametes robiniophila Murr., Polygonatum sibiricum, and Lycium barbarum [35].…”
Section: Discussionmentioning
confidence: 99%
“…HQH can alleviate cyclophosphamide-induced nephrotoxicity by suppressing the MAPK/NF-κB pathway and NLRP3 inflammasome activation [31]. Liu's study showed AKT1, MMP9, and SERPINE1 may be vital in treating HSPN using Network Pharmacology and Molecular Docking Analysis [34]. HQH granules are mainly composed of Trametes robiniophila Murr., Polygonatum sibiricum, and Lycium barbarum [35].…”
Section: Discussionmentioning
confidence: 99%